Customer Value Co-Creation within Partnership Models of Health Care: An Examination of the New Zealand Midwifery Partnership Model. Issue 3 (August 2014) - Krisjanous, Jayne; Maude, Robyn
This exploratory work proposes that partnership models of health care provide a context for customer value co-creation as premised within the framework of Service-Dominant Logic (S-D logic). The main objective of this research is to explore the phenomenon of customer value co-creation within a partnership model of health care and classify the nature of activities clients engage in that might be considered customer value co-creation oriented. The context for this study is the New Zealand midwifery service which delivers health care within a partnership model known as the Midwifery Partnership Model (MPM). The study uses a subjective personal introspection (SPI) approach. Reflection and discussion finds a partnership health care model such as the MPM is facilitative of customer value co-creation. However, models predicated only on a partnership practice style may need broadening in order to be more comprehensive of additional potential value co-creation practice styles within a targeted health market. Our study contributes to the field of customer value co-creation in health by addressing calls for more work in the area. In particular this article focuses on a context where partnership is an underlying premise for service design.